Aortic morphological variability in patients with bicuspid aortic valve and aortic coarctation. (30th October 2018) - Sophocleous, Froso; Biffi, Benedetta; Milano, Elena Giulia; Bruse, Jan; Caputo, Massimo; Rajakaruna, Cha; Schievano, Silvia; Emanueli, Costanza; Bucciarelli-Ducci, Chiara; Biglino, Giovanni
Abstract: OBJECTIVES: This study aimed to explore aortic morphology and the associations between morphological features and cardiovascular function in a population of patients with bicuspid aortic valve, while further assessing differences between patients with repaired coarctation, patients with unrepaired coarctation and patients without coarctation. METHODS: This is a single-centre retrospective study that included patients with available cardiovascular magnetic resonance imaging data and native bicuspid aortic valve diagnosis ( n  = 525). A statistical shape analysis was performed on patients with a 3-dimensional magnetic imaging resonance (MRI) dataset ( n  = 108), deriving 3-dimensional aortic reconstructions and computing a mean aortic shape (template) for the whole population as well as for the 3 subgroups of interest (no coarctation, repaired coarctation and unrepaired coarctation). Shape deformations (modes) were computed and correlated with demographic variables, 2-dimensional MRI measurements and volumetric and functional data. RESULTS: Overall, the results showed that patients with coarctation tended towards a more Gothic arch architecture, with decreased ascending and increased descending aorta diameters, with the unrepaired-aortic coarctation subgroup exhibiting more ascending aorta dilation. Careful assessment of patients with repaired coarctation only revealed that a more Gothic arch, increased descending aorta dimensions and ascending aorta dilation were associated with reduced ejection fraction ( P  ≤ 0.04), increased end-diastolic volume ( P  ≤ 0.04) and increased ventricular mass ( P  ≤ 0.02), with arch morphology distinguishing patients with and without recoarctation ( P  = 0.05). CONCLUSIONS: A statistical shape modelling framework was applied to a bicuspid aortic valve population revealing nuanced differences in arch morphology and demonstrating that morphological features, not immediately described by conventional measurements, can indicate those shape phenotypes associated with compromised function and thus possibly warranting closer follow-up.